2011
DOI: 10.1002/jbm.b.31858
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery chemoembolization in a sheep model: Evaluation of performance and safety of irinotecan eluting beads (DEB‐IRI)

Abstract: The purpose of this study was to evaluate and compare plasma pharmacokinetics, lung tissue concentration, and the potential toxicity of drug eluting beads loaded with irinotecan (DEB-IRI) in a sheep pulmonary artery chemoembolization (PACE) model. Sheep (n = 24) were embolized with DEB-IRI loaded with different doses (0, 20, 50, or 100 mg). Direct pulmonary artery (PA) injections of irinotecan were also performed at two doses (50 or 100 mg; n = 4 sheep). Irinotecan was quantified in plasma and lung tissue (liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…The different microspheres available have been tested in separate preclinical studies but have never been compared in a controlled trial (12)(13)(14)(15)(16). Three studies have evaluated the efficacy of IRI-loaded beads on a single and large VX2 tumor in the liver (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different microspheres available have been tested in separate preclinical studies but have never been compared in a controlled trial (12)(13)(14)(15)(16). Three studies have evaluated the efficacy of IRI-loaded beads on a single and large VX2 tumor in the liver (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Several microspheres loadable with IRI are now proposed: DC Bead ® (DC; Biocompatibles UK Ltd, London, United Kingdom), HepaSphere™ (HS; BioSphere Medical, Roissy-en-France, France), and TANDEM ® (CeloNova BioSciences, Newnan, Georgia). Preclinical trials evaluated the properties of the three products individually but not comparatively (12)(13)(14)(15)(16). One in vitro study suggested slight differences in the physical characteristics or elution properties of the different brands of microspheres (17).…”
mentioning
confidence: 99%
“…Irinotecan inhibits the DNA topoisomerase (13) and is a prodrug with the active metabolite SN-38 (14,15). Several experimental studies have investigated the pharmacokinetics of irinotecan after chemoembolization with DEBIRI (16)(17)(18)(19)(20). Plasma irinotecan levels were 70%-75% lower after embolization with drug-eluting embolic agents than after intra-arterial administration of irinotecan (19).…”
Section: Discussionmentioning
confidence: 99%
“…TANDEM microspheres are nonresorbable polymethacrylate hydrogel particles 75 mm Ϯ 15 in size coated with Polyzene-F. Previous studies (17,23) have shown that the release of irinotecan from DC Bead particles is faster than the release of doxorubicin, which was attributed to weaker ionic interactions between irinotecan and the embolic agents. With DEBIRI, irinotecan elution is controlled by an ion-exchange mechanism between the positively charged irinotecan hydrochloride salt and the sulfonate-containing hydrogel embolic agents (20).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that embolisation was reversible without any early toxicity. Baylatry et al (174) showed in a sheep model that drug eluting beads loaded with irinotecan resulted in lower systemic exposure compared to direct injection of irinotecan into the pulmonary artery. In a rat model of adenocarcinoma lung metastases, chemo-embolisation was compared with ILuP and IV treatment with carboplatin (175).…”
Section: Chemo-embolisation (Embolic Trapping)mentioning
confidence: 99%